Implementation of Smartboard as Evaluation Media in Science Learning through Wordwall Platform at Krandegan State Elementary School - Azizah, Naili Muna; Zanuba As'ada; Naelatus Sifa; Fatmah Nur Hasanah (International Journal of Asian Education, 2025)
Science learning in Indonesian elementary schools is still dominated by conventional methods that reduce student participation, so interactive evaluation innovations through smartboards and Wordwalls are needed. This study aims to analyze the application of smartboards as an evaluation medium in science learning through the Wordwall platform in fifth grade at Krandegan Public Elementary School. This descriptive qualitative study involved a population of fifth grade students and teachers with a purposive sample of one teacher and 25-30 students. The main research instrument was supported by interview guidelines and recordings, analyzed using the Miles and Huberman model with triangulation. The results showed an increase in student participation, motivation, and cognitive-affective-psychomotor engagement through game-based learning, despite infrastructure and teacher readiness constraints. It was concluded that the smartboard-Wordwall integration was effective for interactive evaluation, and teacher training and infrastructure support were recommended